1981
DOI: 10.1017/s0003356100025162
|View full text |Cite
|
Sign up to set email alerts
|

The management of calves on an early-weaning system: the relationship of voluntary water intake to dry feed intake and live-weight gain to 5 weeks

Abstract: 1981). The management of calves on an early-weaning system: the relationship of voluntary water intake to dry feed intake and liveweight gain to 5 weeks. ABSTRACTA trial compared the voluntary water intake of 72 purchased British Friesian bull calves fed at different nutrient intake levels by varying the type and strength of the milk replacer given to 5 weeks of age. There was no control group without water on offer. Water was offered from the 1st day the animals entered the unit. All calves received 4 I/day o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
1
10
0
2
Order By: Relevance
“…The missing satiety of calves fed low volumes of milk was expressed in other trials by considerably more visits to the milk feeder without receiving milk compared to calves fed large volumes of milk (Borderas et al, 2009;de Passillé et al, 2011). It was suggested 30 years ago that calves benefit from the provision of water early in life through improved performance (Thickett et al, 1981). However, ad libitum water access for young calves in Europe is often still not realized at dairy farms because legislation dictates ad libitum water access only for calves older than 2 weeks of life.…”
Section: Feeding Regimes P Feeding Regimementioning
confidence: 99%
See 1 more Smart Citation
“…The missing satiety of calves fed low volumes of milk was expressed in other trials by considerably more visits to the milk feeder without receiving milk compared to calves fed large volumes of milk (Borderas et al, 2009;de Passillé et al, 2011). It was suggested 30 years ago that calves benefit from the provision of water early in life through improved performance (Thickett et al, 1981). However, ad libitum water access for young calves in Europe is often still not realized at dairy farms because legislation dictates ad libitum water access only for calves older than 2 weeks of life.…”
Section: Feeding Regimes P Feeding Regimementioning
confidence: 99%
“…Usually great individual differences between the water intakes of young calves were noticed (Jenny et al, 1978;Thickett et al, 1981;Kertz et al, 1984). This underlines that it is not acceptable to specify an age limit from which calves have to have ad libitum water access.…”
Section: Feeding Regimes P Feeding Regimementioning
confidence: 99%
“…Overall, a lack of scientific evidence on drinking water intake (FWI) of newborn calves and its effect on their performance likely encumbers the effectiveness of efforts promoting the notion of offering drinking water to newborn calves at birth. Thickett et al (1981) indicated the importance in examining the effect of the age at which calves are first offered drinking water. Then, Kertz et al (1984) conducted an observational study using data from several calf trials conducted by Ralston Purina (St. Louis, MO) and demonstrated more than 30% increase in starter intake and weight gain in calves receiving drinking water from birth compared with calves deprived of drinking water until they were 28 d of age.…”
Section: Introductionmentioning
confidence: 99%
“…Reported data on water intake in young calves are scarce. In general, the reported values averaged less than 2 L/d for the first 3 wk and then increased with starter intake and weaning (Thickett et al, 1981;Kertz et al, 1984). A more recent experiment determined that free water intake was similar between 2 MR feeding levels and increased as starter intake increased (Quigley et al, 2006).…”
Section: Resultsmentioning
confidence: 95%
“…In a survey of operations in the United States, the average age water was first offered was 6.6 ± 1.3 d (range 4.1 to 10.6 d) for operations classified as large or small, respectively (USDA, 2012). However, it is important to provide water earlier to dairy calves because they increase the amount of free water they drink after both colostrum intake and transportation (Thickett et al, 1981;Kertz et al, 1984). Soon after arrival, all calves averaged approximately 1.5 L/d of free water intake within the first week of age.…”
Section: Resultsmentioning
confidence: 99%